Bubuka Lawang Dance in Nyiar Lumar as a Media for Cultural Communication in Ciamis - Intandiani, Annastasya Nur; Musunah, Juju; Narawati, Tati (Universitas Negeri Medan, 2024)
Dance performance is not merely a sequence of artistically arranged movements. Instead, a dance performance serves as a cultural communication medium between the creator and the audience. In the presentation of dance, expressed through each movement, there is meaning that goes beyond the physical aspects alone. Whether through harmonious movement or the selection of specific themes, a dance performance acts as a window that opens the audience's view into the world of emotions, values, and stories intended by the creator. The Bubuka Lawang Dance during Nyiar Lumar in Kawali, Ciamis Regency, West Java, showcases a community that continues to preserve and uphold its culture through Nyiar Lumar activities held every two years. Since 1998, Nyiar Lumar has been organized with the aim of building social solidarity through artistic activities in public spaces. This article aims to describe the research findings on the presentation of the Bubuka Lawang Dance during Nyiar Lumar in Kawali, Ciamis Regency. The research method employed is descriptive with a qualitative approach. The results reveal three stages in Nyiar Lumar: ngawalan (Opening ceremony), lalampahan (Journey), and magelaran (Performance). Additionally, there is a distinctive dance always featured during Nyiar Lumar titled